Viruses affecting chia crops and occurrence of cowpea mild mottle virus in chia-producing regions - Luciani, Cecilia Elizabeth (2024)
Chia seeds production has been growing rapidly since mid-2011 when worldwide nutrition experts highlighted the nutritional values of this superfood. However, little is known about the viral diseases affecting this crop can cause yield losses. This study aimed to investigate the epidemiology of cowpea mild mottle virus (CPMMV) in chia crops in northwestern Argentina and to identify and characterize other viruses that infect this crop. Between 2013 and 2021, symptomatic chia leaves and seeds were collected from 480 plants and analyzed for the presence of CPMMV using PTA-ELISA. Transmission through seeds of naturally infected plants was also tested. In addition, total RNA from one CPMMV-positive plant and four CPMMV-negative plants were sequenced by massive sequencing. The results showed that 17% of the chia plants were infected with CPMMV, and the virus incidence varied from 60–80% in the north to 0–5% in the south of the chia-producing fields in the northwestern region, possibly due to variations in the vector population. CPMMV was not detected in any of the 1530 seedlings that developed from the seeds obtained from infected plants. The complete genome of CPMMV was 8180 nucleotides long and shared more than 96.54% nucleotide identity with nine isolates from Brazil and the USA. In addition, the A component of five other begomoviruses were sequenced, including sida mosaic Bolivia virus 2, which is known to infect chia plants, and four other viruses detected in chia for the first time: soybean blistering mosaic virus, tomato mottle leaf distortion virus, tomato dwarf leaf virus, and Euphorbia severe leaf golden mosaic virus. This study also reports the first detection of tomato mottle leaf curl virus in Argentina and the second detection of Euphorbia severe leaf golden mosaic virus in the world. Moreover, this is the second time that an amalgavirus reported to infect chia plants in India, Salvia hispanica RNA virus 1, was sequenced. Overall, this study provides new insights into the epidemiology and molecular detection of CPMMV and other viruses that infect chia crops, which is important for developing effective strategies for the control of these diseases and for maintaining the sustainable production of this important superfood.